A new route for the synthesis of polyaniline nanoarrays on graphene oxide for high-performance supercapacitors. (1st March 2018) - Tabrizi, Amin Goljanian; Arsalani, Nasser; Mohammadi, Abdolkhaled; Ghadimi, Laleh Saleh; Ahadzadeh, Iraj; Namazi, Hassan
Abstract: A traditional approach is conducted for the preparation of polyaniline/graphene oxide (PANI/GO) nanostructures, where aniline monomer followed by ammonium persulfate (APS) were added to an acidic solution of graphene oxide (GO). Herein, we investigate a condition in which firstly GO is dispersed in acidic media containing APS. The aniline monomer is then added in order to the in-situ polymerization of aniline. An investigation is also carried out on the effect of the acid type including sulfuric acid (H2 SO4 ), hydrogen chloride (HCl), perchloric acid (HClO4 ), and p -toluenesulfonic acid (PTSA) on the morphology and electrochemical behavior of resultant PANI/GO nanostructures. The characterizations reveal well-defined nanoarrays for PANI/GO-H2 SO4 electrode with the highest porosity and specific surface area. This electrode exhibits a highest current density in cyclic voltammetry studies and the most specific capacitance (727 F g −1 ) in charge/discharge studies among other as-prepared electrodes. Utilizing this PANI/GO-H2 SO4 nanocomposite as the electrodes in a symmetric configuration resulted in the development of devices with remarkable performance including a maximum energy density of 40 Wh kg −1 and a power density up to 15.3 kW kg −1 with an excellent cycle life (only 4.3% loss after 5000 cycles).